The Effect of Using TikTok Application towards Students’ Speaking Skill at the Tenth Grade Students of SMKN 5 Pandeglang in Academic Year 2022/2023 - Hartini, Reni; Novari, Ari Fajria; Munawaroh, Tatu (Journal of English Education Studies, 2023)
This research aims to investigate the significant effect of using TikTok application towards students’ speaking skill at the tenth grade students of SMKN 5 Pandeglang in academic year 2022/2023. The research used the quantitative approach and quasi-experimental design. This research was conducted from May to June. The researcher has chosen two classes as sample. They are control class and experimental class. The technique in choosing the sample is cluster random sampling, the researcher used X RPL 1 (35 students) as control class and X RPL 2 (35 students) as experimental class. The experimental class was taught by using TikTok application, whereas the control class was taught by using YouTube application. In technique of Collecting the data, the researcher gives pre-test and post-test. The total score of pre-test at control class is 1965. Meanwhile, the total score of the post-test at control class is 2320. The total score of the pre-test at experimental class is 2115. Meanwhile, the total score of the post-test at experimental class is 2335. The mean of the pre-test at control class is 56,14. Meanwhile, the mean of the post-test at control class is 66,29. Then, the mean of the pre-test at experimental class is 60,43. Meanwhile, the mean of the post-test at experimental class is 66,71. In managing the data, the researcher used SPSS 29 statistical computation and used the result of the post-test both class control and experimental to analyze the hypotheses test. The researcher has found the result of Significant two-tailed = 0.000 < α 0.05. Therefore, the researcher concluded that the usage of TikTok application has a significant impact on students’ speaking skill in SMKN 5 Pandeglang.